Josefa Mitterera ucieczka od esencjalizmu - Bińczyk, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2005)
Ewa Bińczyk Josef Mitterer’s Escape from Essentialism In her review of Josef Mitterer’s book “Ucieczka z dowolności”, the Author provides a critical evaluation of the book which proposes to depart from dualist assumptions in the process of communication.